Correlation of 128-Slice Computed Tomography Scan and Autopsy Findings in Fatal Craniocerebral Trauma (Indian Journal of Forensic Medicine & Toxicology, 2025)
BackgroundHead injury remains a major cause of morbidity and mortality worldwide. While computed tomography (CT) scans serve as a critical diagnostic tool in detecting intracranial lesions, forensic autopsy remains the gold standard for definitive assessment. This study evaluates the diagnostic accuracy of 128-slice CT scans in identifying fatal head injuries by comparing imaging findings with autopsy results.MethodsA retrospective observational study was conducted on 60 cases of fatal head injuries admitted to A.J. Institute of Medical Sciences & Research Centre between December 2016 and April 2018. CT scan findings were systematically compared with autopsy results, with a focus on intracranial haemorrhages and contusions. Sensitivity, specificity, and concordance between imaging and post-mortem findings were analyzed using IBM SPSS Statistics (Version 17).ResultsAmong the 60 cases, 90% were males, with road traffic accidents accounting for 86.67% of cases. The sensitivity of CT scans for different types of hemorrhages was as follows: subarachnoid hemorrhage (60.71%), subdural hemorrhage (58%), extradural hemorrhage (40.9%), and intracerebral hemorrhage (11.11%). Contusion detection was highest in the frontal lobe (90.32%) and lowest in the corpus callosum (16.67%). Smaller contusions and posterior cranial fossa lesions were frequently missed on CT scans.ConclusionWhile CT scans play a valuable role in forensic and clinical assessments, they exhibit limitations in detecting smaller hemorrhages and contusions. The study underscores the need for high-resolution imaging, contrast-enhanced CT, and serial imaging to improve diagnostic accuracy. Future research should focus on MRI integration, AI-assisted imaging, and multicentric studies to enhance forensic radiology.
Keywords: Head injury, CT scan, autopsy, forensic radiology, intracranial hemorrhage, contusions, forensic imaging.